Human papillomavirus (HPV) can establish productive infection in dysplastic oral mucosa, but HPV status is poorly predicted by histological features and p16 expression. Issue 4 (24th January 2020) - Hendawi, Naeima; Niklander, Sven; Allsobrook, Olive; Khurram, Syed Ali; Bolt, Robert; Doorbar, John; Speight, Paul M.; Hunter, Keith D.
Abstract : Aims: Previous studies have reported the presence of high‐risk human papillomavirus (HR‐HPV) in a subset of dysplastic oral epithelial lesions. Many cases show a histological spectrum of atypia similar to that seen in non‐human papillomavirus (HPV) severe epithelial dysplasia, but some studies have suggested that HPV status can be inferred on the basis of histological features. We aimed to assess the utility of such histological features and p16 as surrogate markers of HPV infection in a retrospective cohort of 33 cases of severe epithelial dysplasia, with matched clinicopathological data and histological features. Methods and results: Tissue sections were assessed for the expression of p16, minichromosome maintenance 2, HPV E4 and HPV L1 by the use of immunohistochemistry. HPV16/18 E6 and E7 expression was assessed by the use of RNA in‐situ hybridisation (RNAScope). In the cohort, 18.2% of cases (6/33) were HR‐HPV‐positive, with no age/gender differences between the HPV‐positive and HPV‐negative groups. HPV E4 and HPV L1 were expressed in surface keratinocytes in four of six (66%) HPV‐positive cases, indicative of productive HPV infection. Lack of p16 expression was predictive of HPV‐negative status, but sensitivity and specificity varied according to the cut‐off. Histologically, the presence of karyorrhectic nuclei and abnormal mitotic figures was higher in HPV‐positive lesions ( P  < 0.05), but the predictive specificity and sensitivity were suboptimal (sensitivity, 0.75; specificity, 0.52). Conclusions: This study demonstrates, for the first time, that a minority of severely dysplastic oral lesions harbour productive, biologically relevant HPV infection. Consideration should be given to the specific assessment of HPV status in severe epithelial dysplasia cases, as both p16 status and the presence of karyorrhectic cells are poor predictive markers of HPV status.